Behavioral Consequences of Customer Inspiration: The Role of Social Media Inspirational Content and Cultural Orientation (Journal of Informatics Education and Research, 2024)
Although previous studies have emphasized the impact of inspiration on consumer behavior, there is a paucity of knowledge regarding how social media content motivates consumers across various cultures. This study fills that gap through a vignette experimental approach. A vignette study was performed involving 370 people from Nigeria and South Africa. Structural equation modeling, ANOVA, and regression analysis were employed to evaluate scale psychometrics and test hypotheses. The research indicated that hedonic content motivated consumers more than utilitarian content. Collectivist customers exhibited greater inspiration than individualists. Customer inspiration (CI) resulted in heightened customer engagement behaviors (CEBs) and purchase intents, with the "inspired-to" element mitigating the influence of "inspired-by" on both CEBs and purchase intention. The research emphasizes firm-generated content, while future investigations should examine the effects of consumer-generated content and product categories across various interaction scenarios.  The research illustrates the impact of social media content and cultural orientation on consumer involvement (CI), which subsequently affects consumer engagement behaviors (CEBs) and purchase intention, elucidating the psychological mechanisms underlying these actions.